NEW APPROACHES IN DIAGNOSIS AND TREATMENT OF CHRONIC MYELOID LEUKEMIA: FOCUS ON TARGETED THERAPY (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The development of malignant tumor diseases of the blood system is associated with theoccurrence of a number of successive gene mutations leading to the development of a malignantcell clone. It is also known that during therapy, the primary population of malignant cells canacquire secondary mutations, changing under the influence of various selection factors in thepatient's body (immunological selection, the action of cytostatic drugs, etc.)